2020
DOI: 10.1007/s00330-020-07573-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the FUSION-X-US-II prototype to combine automated breast ultrasound and tomosynthesis

Abstract: Objective The FUSION-X-US-II prototype was developed to combine 3D automated breast ultrasound (ABUS) and digital breast tomosynthesis in a single device. We evaluated the performance of ABUS and tomosynthesis in a single examination in a clinical setting. Methods In this prospective feasibility study, digital breast tomosynthesis and ABUS were performed using the FUSION-X-US-II prototype without any change of the breast position in patients referred for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Further work is warranted to develop (more reliable) diagnostic models which combine imaging with comprehensive clinical and demographic data to fully represent the clinical reality (see commonly considered variables according to the National Comprehensive Cancer Network guideline for breast cancer screening [ 5 ]). Moreover, current research evaluates the feasibility of automated breast ultrasound and its combination with digital breast tomosynthesis which may further advance (automated) multi-modal breast image analysis in the future [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further work is warranted to develop (more reliable) diagnostic models which combine imaging with comprehensive clinical and demographic data to fully represent the clinical reality (see commonly considered variables according to the National Comprehensive Cancer Network guideline for breast cancer screening [ 5 ]). Moreover, current research evaluates the feasibility of automated breast ultrasound and its combination with digital breast tomosynthesis which may further advance (automated) multi-modal breast image analysis in the future [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion-X-US is a new device under investigation, combining ABUS and tomosynthesis in one device, aiming to improve workflow in clinical practice. Preliminary results of a prospective study, analyzing 101 patients with this prototype, showed good breast coverage (80.0%) and diagnostic accuracy of ABUS (85.0%), as well as 97.1% lesion identification with the combined system [76].…”
Section: Future Perspectivesmentioning
confidence: 95%
“…In 18 out of 101 scans (17.8%), the image quality was described as being relatively similar to the HHUS, with the exception that no scans were ranked on a level of 5 (equal or higher quality than HHUS). Overall, the combined performance of the tomosynthesis and the ABUS resulted in a sensitivity rate of 97.1% and a specificity of 59.7% [23]. Image quality varied greatly depending on the individual breast shape.…”
Section: Comparison Of Dbt and Abusmentioning
confidence: 96%
“…ABUS had 4 false positive findings and the DBT had 15. According to the presented data, the ABUS showed a higher accuracy rate in comparison to the DBT ( Schäfgen et al, on the other hand, evaluated the performance of the FUSION-X-US-II prototype, which was developed to combine ABUS and DBT screening methods in a single device [23]. In 18 out of 101 scans (17.8%), the image quality was described as being relatively similar to the HHUS, with the exception that no scans were ranked on a level of 5 (equal or higher quality than HHUS).…”
Section: Comparison Of Dbt and Abusmentioning
confidence: 99%